1996
DOI: 10.2494/photopolymer.9.57
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5-Tris(4-(tert-Butoxycarbonylmethoxy)-phenyl)benzene as a Novel Electron-beam Positive Resist for Nanometer Lithography.

Abstract: The minimum feature size in semiconductor devices is becoming smaller and smaller. A 0.35 µm resolution is required for the fabrication of 64 Mbit DRAM, and nanometer-size lithographic patterns will be required in the future. One of the factors determining the resolution limit of the lithography process is the particle size of resist materials. In order to obtain nanometer-size lithographic patterns, it is desirable to reduce particle size of the resist materials. Organic polymers have been used as resist mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…150 nm and 70 nm, respectively. [4][5][6] Related to our studies, an oligomer of a calixarene derivative has also been reported to function as a negative electron-beam resist with high resolution. [7] We report here the creation of a novel molecular resist material, 1,3,5-tris[4-(2-tent-butoxycarbonyloxy) phenyl] benzene (o-BCOTPB).…”
supporting
confidence: 61%
“…150 nm and 70 nm, respectively. [4][5][6] Related to our studies, an oligomer of a calixarene derivative has also been reported to function as a negative electron-beam resist with high resolution. [7] We report here the creation of a novel molecular resist material, 1,3,5-tris[4-(2-tent-butoxycarbonyloxy) phenyl] benzene (o-BCOTPB).…”
supporting
confidence: 61%
“…150 nm and 70 nm, respectively. [ 1,2] An oligomer of a calixarene derivative has also been reported to function as a negative electron-beam resist with high resolution. [3] We report here a novel molecular resist material, 1,3,5-tris[4-(4-vinylphenylcarbonyloxy)phenyl]benzene (VCTPB).…”
mentioning
confidence: 99%
“…However, there is a serious problem among the resolution of pattern, sensitivity of the photo-chemical reaction, and roughness of the pattern, i.e., these relationships are well known as "trade-off". To overcome this "trade-off", many molecular glasses such as calixarenes, 1-10 dendritic oligomers, [11][12][13][14][15][16][17][18] low-molecular-weight oligomers, 19,20 and fullerenes 21 have been reported and their resolutions showed about 50 nm regions. Recently, we could design a ladder type cyclic oligomer "noria" (noria = water wheel in Latin), 22 and examined the synthesis, physical properties, and patterning properties of noria derivatives with pendant t-butyl ester groups, 23,24 t-butyloxycarbonyl groups, 25 adamantyl ester groups, 26,27 cyclohexyl acetal moiety, 28 and oxetanyl groups 29 using electron beam (EB) or EUV exposure systems.…”
Section: Introductionmentioning
confidence: 99%